OPTIMALISASI PENYELENGGARAAN PELATIHAN GUNA MENINGKATKAN KEMAMPUAN TEMPUR PRAJURIT TNI AL DALAM RANGKA MENDUKUNG PELAKSANAAN TUGAS POKOK KOMANDO ARMADA RI KAWASAN TIMUR (STUDI DI SATUAN KAPAL AMFIBI) - , WIDODO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this is to describe the combat capability that can be achieved by the Soldiers of the Navy, training events that have been implemented to enhance the combat capability of Navy Soldiers, and efforts to optimize the implementation of training to improve the combat capability of the Navy in Amphibious Ship Unit Soldiers Koarmatim. Based on the objectives to be achieved, so the research applies the naturalistic qualitative approach by using data collection method which involved: participant observation, in-depth interviews and document search. Technical Data analysis using qualitative descriptive techniques through three lanes of activities, include: reduction, data display and conclusion. The obtained findings can be described as follows: First, Mastery of navy soldier combat capability of Eastern Fleet Command Amphibious Warship Unit Koarmatim demonstrate achievement of combat capability with sufficient skilled category. But there are capabilities items that need to be improved, including: the ability to coordinate inter sections, work productivity of Navy Soldiers, Navy personnel skills in repairing damaged equipment of ships and aircraft, and Navy personnel understanding of safety factors and work procedures. Second, The refinement of pattern, method and training organization can be implemented through the revising of the Amphibious warship unit Task Force Rehearsal Implementation manual book that was passed by Chief of Indonesian Navy Decision Number Skep/3243/VII/1989 dated July 18, 1989 to conform the needs, circumstances and current conditions. However, the content of the material as a whole does not need to be revised. Third, in the implementation of training, there are still barriers, such as: the minimum training budgets, the limitation of human resources, the old technology and weaponry systems, as well as inadequate of facility and infrastructure. These obstacles can be overcome through: the effective and efficient training budget management through the the submission of programs and activities that can increase the Navy Soldiers combat capability, human resource development through the fulfillment of the ideal List of Personnel and the upgrading of the human resources, development of technology and weaponry systems through procurement of modern equipment and weaponry systems to support strategic national defense industry, increasing good quality of facilities and infrastructure to support training events through the addition of the infrastructure mainly related training materials which can be used effectively and efficiently. Key Words: Optimization, Training implementation, Combat capability